Penerapan Pendekatan Sains Teknologi Masyarakat Pada Materi Daur Air Dalam Meningkatkan Hasil Belajar Siswa SD Negeri 10 Manurunge Kabupaten Bone - Sakka Sakka (Universitas Negeri Makassar, 2017)
This study used a qualitative approach and type of classroom action research. The formulation of the problem of this research is whether the application of the Community Science Science approach to the water cycle material can improve the learning outcomes of the students of Grade 6A SD Negeri 10 Manurunge? And how is the process of applying the Community Technology Science approach to the water cycle material in improving students' learning outcomes in Grade 6A SD Negeri 10 Manurunge? The purpose of this research is to improve student learning result of Grade 6A SD Negeri 10 Manurunge on water cycle material through application of Science Community Technology approach, as well as to improve the process / activity of learning water cycle material through application of Science Community Technology approach 6A SD Negeri 10 Manurunge. The object of this research is the students of Grade 6A SD Negeri 10 Manurunge. Efforts made to improve students' understanding of the concept of water cycle is to carry out learning at the core stage through four phases: the invitation phase, the exploration phase, the solution phase and the application phase. Data collection techniques used were teacher and student observation, and documentation. Based on the results of analysis and evaluation at the reflection stage, the results showed that, the application of Science Community Technology approaches effectively improve the process / activity and learning outcomes in the Water Recycle material in every cycle of action.